Small group training as an effort to reduce stunting on toddlers in the working area of Puskesmas Kandang Sapi, Pasuruan - Peter Prayogo Hsieh; Christianto Samuel Pieter Tangkau; Helviansyah El Farizqi; Ahmad Shohib (Intisari Sains Medis, 2022)
Background: The World Health Organization (WHO) said that South East Asia has a high stunting prevalence, where it is estimated that 22.2% of toddlers are stunted globally. The reality is that there are still many cases of inaccurate measurement methods, which question the validity of stunting prevalence. This study aims to know if small group training is effective in reducing stunting prevalence in toddlers. Methods: This descriptive study was done at all Posyandu in Bugul Lor from August to September 2019. Populations in this study were all helpers at Posyandu. Samples in this study were all helpers who met inclusive criteria but didn’t meet exclusive criteria. The inclusion criteria were helpers who attended when the study was conducted (5 helpers in each Posyandu), and the exclusive criteria were illiterate helpers. We used measurement guidelines from IDAI. The Group workshop started with a briefing about making sure that all tools were correctly set. Next, all helpers were asked to do height measurements, and if there was any error, we showed them how to do it correctly and let them do it again. We then compared the data before and after the intervention. Data from February 2019 were used as data before the intervention. Results: No helper in 10 Posyandu measured correctly. But after the group workshop, a helper from 8 Posyandu could measure correctly. Stunting prevalence in Bugul Lor decreased by about 4%. Conclusion: Group workshop seems to be effective in reducing stunting prevalence in toddlers.